Diverse functional manifestations of intrinsic structural disorder in molecular chaperones. (19th September 2012) - Kovacs, Denes; Tompa, Peter
Abstract : IDPs (intrinsically disordered proteins) represent a unique class of proteins which show diverse molecular mechanisms in key biological functions. The aim of the present mini-review is to summarize IDP chaperones that have increasingly been studied in the last few years, by focusing on the role of intrinsic disorder in their molecular mechanism. Disordered regions in both globular and disordered chaperones are often involved directly in chaperone action, either by modulating activity or through direct involvement in substrate identification and binding. They might also be responsible for the subcellular localization of the protein. In outlining the state of the art, we survey known IDP chaperones discussing the following points: (i) globular chaperones that have an experimentally proven functional disordered region(s), (ii) chaperones that are completely disordered along their entire length, and (iii) the possible mechanisms of action of disordered chaperones. Through all of these details, we chart out how far the field has progressed, only to emphasize the long road ahead before the chaperone function can be firmly established as part of the physiological mechanistic arsenal of the emerging group of IDPs.